Beliefs and attitudes about opioid prescribing and chronic pain management: Survey of primary care providers - Jamison, PhD, Robert N.; Sheehan, BA, Kerry Anne; Scanlan, NP, Elizabeth; Matthews, PharmD, Michele; Ross, MD, Edgar L. (Journal of Opioid Management, 2014)
Objective: There is growing concern of medication misuse and noncompliance among patients with chronic pain prescribed opioids for pain. The aim of this survey was to obtain information from primary care providers (PCPs) about their perception of prescribing opioids for patients with chronic pain. Methods: PCPs were invited to complete a packet of questionnaires about attitudes and concerns about opioids for chronic pain. These questionnaires included 1) General Health Questionnaire, 2) Test of Opioid Knowledge (TOK), 3) Opioid Therapy Provider Survey, and 4) Concerns About Analgesic Prescription Questionnaire. Results: Fifty-six (N = 56) PCPs from eight centers participated in this study. In general, the PCPs showed adequate opioid knowledge on the KOT and their general health was unrelated to prescription attitudes. Most expressed concern about medication misuse (89 percent) and felt that managing patients with chronic pain was stressful (84 percent). Most were worried about addiction (82 percent) and less than half felt that they were sufficiently trained in prescribing opioids (46 percent). Younger providers felt more reluctant to prescribe opioids, experienced more stress in managing patients with pain, had less overall confidence in managing patients with pain, and worried more about opioid dependence than older providers (p < 0.05). Younger providers were also less knowledgeable about opioids, but opioid knowledge was not found to be related to concerns about analgesic prescriptions. Conclusion: This study indicates a general concern and reluctance of primary care physicians to manage the prescribing of opioids among their patients with chronic pain and younger providers expressed more concern about opioids than older providers.